Towards a privacy impact assessment methodology to support the requirements of the general data protection regulation in a big data analytics context: A systematic literature review. Issue 44 (April 2022) - Georgiadis, Georgios; Poels, Geert
Abstract: Big Data Analytics enables today's businesses and organisations to process and utilise the raw data that is generated on a daily basis. While Big Data Analytics has improved efficiency and created many opportunities, it has also increased the risk of personal data being compromised or breached. The General Data Protection Regulation (GDPR) mandates Data Protection Impact Assessment (DPIA) as a means of identifying appropriate controls to mitigate risks associated with the protection of personal data. However, little is currently known about how to conduct such a DPIA in a Big Data Analytics context. To this end, we conducted a systematic literature review with the aim of identifying privacy and data protection risks specific to the Big Data Analytics context that could negatively impact individuals' rights and freedoms when they occur. Based on a sample of 159 articles, we applied a thematic analysis to all identified risks which resulted in the definition of nine Privacy Touch Points that summarise the identified risks. The coverage of these Privacy Touch Points was then analysed for ten Privacy Impact Assessment (PIA) methodologies. The insights gained from our analysis will inform the next phase of our research, in which we aim to develop a comprehensive DPIA methodology that will enable data processors and data controllers to identify, analyse and mitigate privacy and data protection risks when storing and processing data involving Big Data Analytics.